Pengaruh Pemberian Informasi Covid-19 Dengan Metode Demonstrasi Terhadap Perilaku Masyarakat di Puskesmas Bestari Kecamatan Medan Petisah - Irma Juliana Tanjung; Mappeaty Nyorong; Endang Maryanti (Jurnal Kesehatan dan Fisioterapi, 2023)
Abstract-The public's ignorance of Covid-19 information was related to the provision of information provided by officers at the Bestari Health Center. This study aimed to analyze the effect of providing information on covid 19 with the demonstration method on Community Behavior in the Bestari Health Center, Medan Petisah. This research was a quantitative Quasy-Experimental type with a one group pretest-posttest design that takes place from October to September 2021. The research sample uses purposive sampling, namely some of the people who visit the Bestari Health Center, Medan Petisah, as many as 89 peoples. The survey data were analyzed using the t-test.  The results of the univariate studied showed that from 89 respondents, most of the respondents were 36-45 years old, as many as 33 (37.1%) respondents, female as many as 50 (56.2%) respondents, with bachelor education as many as 47 (52, 9%) of respondents, have a job as self-employed as many as 53 (59.6%) respondents The bivariate results showed that there was an effect of providing information on Covid-19 with the demonstration method on public knowledge, there was an effect of providing information on Covid-19 with the demonstration method on people's attitudes, there was an effect of providing information on Covid-19 with the demonstration method on community actions in the work area of the Bestari Health Center. Medan Petisah District (p=0.000).  Based on the results of the study, it was concluded that the providing of information on Covid-19 with the demonstration method had an effect on the knowledge, attitudes and actions of the community. It is recommended that this research can be used as input for conducting counseling with the demonstration method so that people can understand more quickly what is conveyed by health workers. Keywords: Knowledge,  Attitude,  Action,  Demonstration Method, Covid-19